Mapping energy poverty indices in urban scale: a case study of Santiago de Chile - Martínez-Soto, Aner; Sanhueza-Catalán, Daniel; Uribe-Vargas, Tomas; Lehmann, Rosa; Zipf, Alexander; Sierra-Varela, Leonardo; Nix, Emily; Oyarzún, Tamara (Energy research & social science, 2025)
This study assesses energy poverty in urban contexts using Santiago, Chile, as a case study. Based on a systematic literature review, 15 energy poverty indices were selected and adapted, originally developed for national contexts, to capture local and urban particularities. Using QGIS, the spatial distribution of energy poverty in Santiago was mapped, revealing significant differences depending on the index applied. For instance, the Low Income High Cost index classifies only 3 % of the municipalities as “energy poor,” while the Energy Poverty Index identifies 55 % in this condition. The overall average classification for the entire city was 2.8 (intermediate poverty), with standard deviations ranging from 0.7 (Minimum income standard) to 1.5 (Hidden Energy Poverty and Fuel Poverty Index), highlighting disparities in the indices' ability to capture energy vulnerability. The results emphasize the need to adapt indices to specific urban contexts to avoid interpretative distortions. It is concluded that multidimensional approaches, like the Energy Poverty Index, allow for a more comprehensive assessment of energy poverty and provide a solid basis for guiding interventions that promote energy equity in highly heterogeneous urban settings.